2019
DOI: 10.1002/mus.26620
|View full text |Cite
|
Sign up to set email alerts
|

Class I and II histone deacetylase expression is not altered in human amyotrophic lateral sclerosis: Neuropathological and positron emission tomography molecular neuroimaging evidence

Abstract: Introduction There is an unmet need for mechanism‐based biomarkers and effective disease modifying treatments in amyotrophic lateral sclerosis (ALS). Previous findings have provided evidence that histone deacetylases (HDAC) are altered in ALS, providing a rationale for testing HDAC inhibitors as a therapeutic option. Methods We measured class I and II HDAC protein and transcript levels together with acetylation levels of downstream substrates by using Western blotting in postmortem tissue of ALS and controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In line with this, histone hypoacetylation was an associated feature in ALS models (Bennett et al, 2019; Del Signore et al, 2009; Ryu et al, 2005). However, these findings were not confirmed in an in vivo brain imaging study with a pan‐HDAC PET imaging ligand reported by Dios et al (2019). To analyse the potential of HDACs as biomarkers, the authors investigated class I and II HDAC protein and transcription levels in post‐mortem motor cortex and spinal cord samples, combining this with an in vivo [ 11 C]Martinostat (Figure 1d) study, comparing ALS patients and healthy controls.…”
Section: Imaging Studies Of Hdacsmentioning
confidence: 66%
See 3 more Smart Citations
“…In line with this, histone hypoacetylation was an associated feature in ALS models (Bennett et al, 2019; Del Signore et al, 2009; Ryu et al, 2005). However, these findings were not confirmed in an in vivo brain imaging study with a pan‐HDAC PET imaging ligand reported by Dios et al (2019). To analyse the potential of HDACs as biomarkers, the authors investigated class I and II HDAC protein and transcription levels in post‐mortem motor cortex and spinal cord samples, combining this with an in vivo [ 11 C]Martinostat (Figure 1d) study, comparing ALS patients and healthy controls.…”
Section: Imaging Studies Of Hdacsmentioning
confidence: 66%
“…Ample evidence links decreased histone deacetylation to neurodegeneration (Rouaux et al, 2003;Valle et al, 2014). In line with this, histone hypoacetylation was an associated feature in ALS models (Bennett et al, 2019;Del Signore et al, 2009;Ryu et al, 2005 (Dios et al, 2019). This is in contrast to earlier findings of other groups reporting HDAC differences on protein or mRNA expression levels (Janssen et al, 2010;Körner et al, 2013).…”
Section: Imaging Studies Of Hdacsmentioning
confidence: 77%
See 2 more Smart Citations
“…Histone extracts were obtained from XDP and control post-mortem PFC as well as XDPand control-derived fibroblasts as previously reported [54,55]. Briefly, tissues and cells were homogenized in 5% Triton buffer on ice and centrifuged at 500 g for 8 min at 4˚C to extract nuclei.…”
Section: Histone Extractionsmentioning
confidence: 99%